Hollywood Enlists!: Propaganda Films of World War II - Donald, Ralph (Rowman & Littlefield Publishers, 2017)
Frequently referred to as “the Greatest Generation,” Americans of the World War II era were influenced by Hollywood’s depictions of their nation, its role in world affairs, and the virtue of its involvement in the war. Stories of the bravery and heroism of the American military—as well as the moral and political threat posed by the enemy—filled movie screens across the country to garner passionate support for wartime policies. In Hollywood Enlists! Propaganda Films of World War II, Ralph Donald explores how the studios supported the war effort and helped shape the attitudes of an entire generation. Through films the studios appealed to the public’s sense of nationalism, demonized the enemy, and stressed that wartime sacrifices would result in triumph. The author contends that American films of the period used sophisticated, but often overlooked, strategies of propaganda to ideologically unite the country. While these strategies have long been associated with political speeches and writings during the war, little in-depth consideration has been given to their use in the era’s cinema. By examining major motion pictures—including Casablanca, The Flying Tigers, Mrs. Miniver, Sergeant York, They Were Expendable, and many others—Donald illustrates how various propaganda techniques aligned the nation’s entertainment with government aims. Hollywood Enlists! will appeal to readers with interests in war films and motion picture history, as well as politics and social history.